An Explicit Creep-Fatigue Model for Engineering Design Purposes - Dan Liu; Dirk John Pons (Metals, 2018)
Background: Creep-fatigue phenomena are complex and difficult to model in ways that are useful from an engineering design perspective. Existing empirical-based models can be difficult to apply in practice, have poor accuracy, and lack economy. Need: There is a need to improve on the ability to predict creep-fatigue life, and do so in a way that is applicable to engineering design. Method: The present work modified the unified creep-fatigue model of Liu and Pons by introducing the parameters of temperature and cyclic time into the exponent component. The relationships between them were extracted by investigating creep behavior, and then a reference condition was introduced. Outcomes: The modified formulation was successfully validated on the materials of 63Sn37Pb solder and stainless steel 316. It was also compared against several other models. The results indicate that the explicit model presents better ability to predict fatigue life for both the creep fatigue and pure fatigue situations. Originality: The explicit model has the following beneficial attributes: Integration—it provides one formulation that covers the full range of conditions from pure fatigue, to creep fatigue, then to pure creep; Unified—it accommodates multiple temperatures, multiple cyclic times, and multiple metallic materials; Natural origin—it provides some physical basis for the structure of the formulation, in its consistency with diffusion-creep behavior, the plastic zone around the crack tip, and fatigue capacity; Economy—although two more coefficients were introduced into the explicit model, the economy is not significantly impacted; Applicability—the explicit model is applicable to engineering design for both manual engineering calculations and finite element analysis. The overall contribution is that the explicit model provides improved ability to predict fatigue life for both the creep-fatigue and pure-fatigue conditions for engineering design.